2014
DOI: 10.1002/anie.201400135
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Synthesis of Alkenyl Tetrazines for Highly Fluorogenic Bioorthogonal Live‐Cell Imaging Probes

Abstract: In spite of the wide application potential of 1,2,4,5-tetrazines, particularly in live-cell and in-vivo imaging, a major limitation has been the lack of practical synthetic methods. Here we report the in situ synthesis of (E)-3-substituted-6-alkenyl-1,2,4,5-tetrazine derivatives via an elimination-Heck cascade reaction. Using this strategy, we provide 24 examples of π-conjugated tetrazine derivatives that can be conveniently prepared from tetrazine building blocks and related halides. These include tetrazine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
167
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(173 citation statements)
references
References 52 publications
2
167
0
4
Order By: Relevance
“…Increasing the strain in the trans -cyclooctene moiety through cyclopropyl fusion resulted in a 50-fold rate enhancement (Lang et al, 2012b; Seitchik et al, 2012). Additionally, π-conjugated tetrazines exhibit strong fluorescence upon cycloadditions with dienophiles such as cyclopropenes and trans-cycloctene (Wu et al, 2014). Applications of tetrazine-TCO ligations have included labeling of newly synthesized proteins (Lang et al, 2012a) and cancer cells (Devaraj et al, 2010; Devaraj et al, 2009), in vivo cancer imaging with 111 In (Rossin et al, 2010) and 18 F radiolabeling (Keliher et al, 2011; Li et al, 2010; Reiner et al, 2011), cancer cell detection (Haun et al, 2010), fluorescent imaging of cytoskeletal proteins within living mammalian cells (Liu et al, 2012), and recently the methodology has been used with amino acids modified by tetrazine (Seitchik et al, 2012) and trans -cyclooctene (Lang et al, 2012b) for genetic incorporation into proteins.…”
Section: B Bioorthogonal Conjugation Strategies and Applicationsmentioning
confidence: 99%
“…Increasing the strain in the trans -cyclooctene moiety through cyclopropyl fusion resulted in a 50-fold rate enhancement (Lang et al, 2012b; Seitchik et al, 2012). Additionally, π-conjugated tetrazines exhibit strong fluorescence upon cycloadditions with dienophiles such as cyclopropenes and trans-cycloctene (Wu et al, 2014). Applications of tetrazine-TCO ligations have included labeling of newly synthesized proteins (Lang et al, 2012a) and cancer cells (Devaraj et al, 2010; Devaraj et al, 2009), in vivo cancer imaging with 111 In (Rossin et al, 2010) and 18 F radiolabeling (Keliher et al, 2011; Li et al, 2010; Reiner et al, 2011), cancer cell detection (Haun et al, 2010), fluorescent imaging of cytoskeletal proteins within living mammalian cells (Liu et al, 2012), and recently the methodology has been used with amino acids modified by tetrazine (Seitchik et al, 2012) and trans -cyclooctene (Lang et al, 2012b) for genetic incorporation into proteins.…”
Section: B Bioorthogonal Conjugation Strategies and Applicationsmentioning
confidence: 99%
“…Several groups have reported fluorogenic tetrazine probes that fluoresce upon reacting with strained alkenes and alkynes. [8] We were drawn to a recent study in which Devaraj and co-workers reported para-vinylenemethyltetrazines that exhibit up to 400-fold fluorescence turn-on; [9] we expected these tetrazines to be stable for at least several hours in serum, [10] making them good candidates for in vivo imaging experiments. Tetrazines are known to react with a variety of strained unsaturated hydrocarbons, including norbornene, [11] cyclopropene, [8c, 12] cyclooctyne, [8b,13] and trans-cyclooctene.…”
mentioning
confidence: 99%
“…[16] Furthermore, several studies across different classes of fluorophores have shown that the pyridazine products resulting from alkyne-tetrazine cycloadditions are brighter than the dihydropyridazine products resulting from alkene-tetrazine cycloadditions. [9,17] Aside from its beneficial attributes, cyclooctyne has a liability as a chemical reporter: It is large relative to a monosaccharide substrate, unlike azides and terminal alkynes, the more common chemical reporters for glycan imaging. Indeed, unnatural monosaccharides containing modifications larger than a few atoms are generally poor substrates for the biosynthetic enzymes that enable their incorporation into glycans.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Not only can the fluorous oxidant reported here be used to label arylstannanes and proteins, it was also shown to be very effective for producing functionalized tetrazines, which are emerging as highly effective synthons for bioorthogonal labeling reactions. [25][26][27][28] …”
Section: Introductionmentioning
confidence: 99%